The effect of audience presence on home advantage: An analysis of two seasons in the Moroccan professional soccer league - Atifi, J.; Lotfi, S. (Journal of Physical Education and Sport, 2024)
The home advantage in soccer is often attributed to the presence of spectators. The recent pandemic, which led to matches being played without audiences, provides a unique opportunity to explore this hypothesis in the Moroccan professional soccer league. This study aims to analyze the impact of audience presence on match outcomes by comparing two seasons: 2018/2019 (with spectators) and 2020/2021 (without spectators, during the SARS-CoV-2 pandemic). The goal is to determine whether the absence of an audience significantly affects team performance at their home stadium. The study presents an analysis of the results of 390 soccer matches that were played over the course of two seasons. The variables examined include the number of wins, losses, and draws, as well as the number of goals scored and conceded. A two-factor analysis of variance (ANOVA II) was employed to assess the impact of audience presence and match location.